T-Pebbling in k-connected graphs with a universal vertex - Alcón, Liliana Graciela (2019)
The t-pebbling number is the smallest integer m so that any initially distributed supply of m pebbles can place t pebbles on any target vertex via pebbling moves. The 1-pebbling number of diameter 2 graphs is well-studied. Here we investigate the t-pebbling number of diameter 2 graphs under the lens of connectivity.